ABA Enhances Drought Resistance During Rapeseed (Brassica napus L.) Seed Germination Through the Gene Regulatory Network Mediated by ABA Insensitive 5 - Dan Luo; Qian Huang; Manyi Chen; Haibo Li; Guangyuan Lu; Huimin Feng; Yan Lv (Plants)
ABA Insensitive 5 (ABI5) is a basic leucine zipper (bZIP) transcription factor (TF) that plays a critical role in seed dormancy and germination, particularly under stress conditions. This study identified ABI5 as an important candidate gene regulating seed germination under drought stress during early germination in rapeseed (Brassica napus L.) seeds through Genome-Wide Association Study (GWAS). Using Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/CAS9) technology, ABI5 mutant plants were generated, showing higher germination rates and more developed root systems at 72 h. Transcriptomic analysis of wild-type (WT) and mutant seeds under water, 2μM of abscisic acid (ABA), and 10% PEG treatments after 0, 24, 48, and 72 h revealed complex changes in gene regulatory networks due to ABI5 mutation. Differential expression analysis showed that the number of downregulated differentially expressed genes (DEGs) in the mutant was significantly higher than upregulated DEGs at multiple time points and treatments, indicating a negative regulatory role for ABI5 in gene expression. Weighted Gene Co-Expression Network Analysis (WGCNA) revealed that genes related to ABA content, such as those in the glutathione metabolism pathway, were similarly downregulated in the ABI5 mutants. Key genes, including BnA03g0120550.1 (GST), BnA09g0366300.1 (GST), BnA10g0413960.1 (gshA), and BnC02g0518750.1 (GST), were identified as potential candidates in ABI5-regulated drought responses. Additionally, TFs involved in regulating the glutathione metabolism pathway were identified, providing insights into the collaboration of ABI5 with other TF. This comprehensive transcriptomic analysis of ABI5 mutant plants highlights how ABI5 affects gene expression in multiple pathways, impacting seed germination and drought resistance, offering a foundation for improving drought tolerance in rapeseed.